Altered cortical processing of motor inhibition in schizophrenia. (December 2016) - Lindberg, Påvel G.; Térémetz, Maxime; Charron, Sylvain; Kebir, Oussama; Saby, Agathe; Bendjemaa, Narjes; Lion, Stéphanie; Crépon, Benoît; Gaillard, Raphaël; Oppenheim, Catherine; Krebs, Marie-Odile; Amado, Isabelle
Abstract: Inhibition is considered a key mechanism in schizophrenia. Short-latency intracortical inhibition (SICI) in the motor cortex is reduced in schizophrenia and is considered to reflect locally deficient γ-aminobutyric acid (GABA)-ergic modulation. However, it remains unclear how SICI is modulated during motor inhibition and how it relates to neural processing in other cortical areas. Here we studied motor inhibition Stop signal task (SST) in stabilized patients with schizophrenia ( N = 28), healthy siblings ( N = 21) and healthy controls ( n = 31) matched in general cognitive status and educational level. Transcranial magnetic stimulation (TMS) and functional magnetic resonance imaging (fMRI) were used to investigate neural correlates of motor inhibition. SST performance was similar in patients and controls. SICI was modulated by the task as expected in healthy controls and siblings but was reduced in patients with schizophrenia during inhibition despite equivalent motor inhibition performance. fMRI showed greater prefrontal and premotor activation during motor inhibition in schizophrenia. Task-related modulation of SICI was higher in subjects who showed less inhibition-related activity in pre-supplementary motor area (SMA) and cingulate motor area. An exploratory genetic analysis of selected markers of inhibition (GABRB2, GAD1, GRM1, and GRM3) did not explain task-related differences in SICI or cortical activation. In conclusion, this multimodal study provides direct evidence of a task-related deficiency in SICI modulation in schizophrenia likely reflecting deficient GABA-A related processing in motor cortex. Compensatory activation of premotor areas may explain similar motor inhibition in patients despite local deficits in intracortical processing. Task-related modulation of SICI may serve as a useful non-invasive GABAergic marker in development of therapeutic strategies in schizophrenia.